Mini-review: red seaweed Hydropuntia edulis and agar derivatives for food, medicinal and agriculture applications - Tracy, Saptu; Kaiser, Mahmood; Leong, Wan-Teng; Mohd Fakhrulddin, Ismail; Irina, Harun; Uthumporn, Utra; Ahmad, Husaini; Shahrul Razid, Sarbini; Muta Harah, Zakaria; Yus Aniza, Yusof; Shiamala Devi, Ramaiya; Hanisah Kamilah, Abd Razak (PeerJ Inc., 2026)
The red seaweed Hydropuntia edulis is found in Southeast Asia in the Indian and Pacific Oceans. Due to ease of cultivation and a greater concentration of sulfated polysaccharides, H. edulis is a superior source for agar production compared to other species. However, the pretreatments and extraction conditions strongly impact agar's final gel strength and yield. Agar is made up of agarose, which is approximately 70%, and agaropectin, 30%, and has found a wide range of applications as a thickening, gelling, and stabilizing agent. This review highlighted agar extraction, its application in food as an ingredient, coating, and packaging. In-depth discussions about the interaction of agar with non-agar biopolymers have been made to diversify its utility in different avenues. Additionally, by considering the richness of bioactive derivatives of H. edulis, the applications in pharmaceuticals, agriculture, and aquaculture have been elaborated, followed by some limitations. Detailed investigation of H. edulis review aims to encourage increased cultivation of the species for producing agar and other bioactive compounds that support sustainable food, pharmaceutical, agriculture, and aquaculture industries.